Effects Of Covid-19 Pandemic On The Host Communities Of Rohtak, Haryana And Durgapur, West Bengal (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The ongoing pandemic has caused severe crisis in the hospitality sector with  millions of people forced to stay home and under quarantine to stop the spread of contagion.  The following paper aims to highlight the problems and difficulties faced by the hospitality  sector and the host communities in particular due to the mandatory nation-wide lockdown  owing to COVID-19 pandemic. Objective: The purpose of the study was to analyse and  highlight the common characteristics of the host community towards the stranded  international and domestic travellers while catering and accommodating them owing to local  authorities’ obligatory lockdown along with the forced shutdown of hotels and large  commercial establishments in Rohtak and Durgapur. Methodology: The geographical area  of the research and data collection was limited to the city of Rohtak in Haryana and  Durgapur in the state of West Bengal. Population of the study is limited to the region of  Rohtak and Durgapur. The number of participants or respondents were 42.The paper is  exploratory in design and follows a qualitative methodological approach. The data was collected with the help of an online self-report questionnaire. Results: Over a period of 95  days, the interviews of hosts and tourists were conducted. The content analysis revealed eight  themes in all the recorded interviews. A majority of tourists and host communities were  impacted by the pandemic in psychological aspects by 35.7%, followed by accommodation  and protocols by 33.3% each. Conclusion: There have been various studies that have been  conducted in the backdrop of COVID-19 pandemic but not many of them have highlighted the  importance of host communities which are an indispensable part of our society as well as the  hospitality sector.
Keywords: COVID-19; Pandemic; Host Community; Lockdown